Organizational power and well-being at work: some differences between man and women employed in higher education institutions - Slišković, Ana (Array, 2013)
Formal power, which is determined by the position in the organizational hierarchy and by the type of working contract, is positive, but not directly associated with well-being at work. A significant mediator of this relationship is the experience of control in the workplace. Based on the knowledge of traditional gender roles and the underrepresentation of women in leadership positions, it is reasonable to assume that women use the objective position of power to gain control in the workplace in a lower extent. Therefore, it can be expected that the experience of work control in women 1) will show a slower increase with increase in the objective power, 2) on average will be lower, compared to experience of work control in men, and 3) women will ultimately show lower well-being at work than men. The objective power of employees in higher education institutions is defined primarily through six positions, which are also the steps in research and teaching advancement (assistant, senior assistant, assistant professor, associate professor, full professor, and full professor with tenure). Testing was conducted using an online survey on a sample of 1158 university teachers, of whom 57% were women. Work locus of control, job satisfaction, satisfaction with the organization and psychological well-being were measured by the Pressure Management Inventory (Williams and Cooper, 1998). Results of two-way ANOVAs, 6 (Position) * 2 (Gender), show the expected significant effects of the employees’ position on job and organizational satisfaction and psychological well-being, whereby significant gender differences were obtained for organizational satisfaction and psychological well-being. Women reported poorer psychological well-being and were less satisfied with the organization. Women and the teachers in the lower positions on average also reported the lower experience of work control. Obtained results show interactive effects of gender and position on the satisfaction with organization, where the growth of the organizational satisfaction with the growth of formal power in women is less pronounced. These results support the assumption that the lower level of well-being in women in higher education can be partly explained by a lower experience of work control.